Striped catfish oil and turmeric extract reduces inflammation in metabolic syndrome rats - Mambaya, Helvi Desi; Muniroh, Muflihatul; Afifah, Diana Nur; Anjani, Gemala; Pramono, Adriyan; Sulchan, Mohammad (International Journal of Public Health Science (IJPHS), 2025)
Metabolic syndrome is a growing global health problem. Long-term treatment for metabolic syndrome causes side effects. Therefore, the use of nutraceuticals could also be considered. This study analyzed the effect of the administration of striped catfish oil and turmeric extract on tumor necrosis factor-α (TNF-α) levels and homeostasis model assessment of insulin resistance (HOMA-IR) in metabolic syndrome rats. Metabolic syndrome was induced in rats by administration of high fat fructose diet (HFFD) containing 3 g pork fat (15%), 2 g duck egg yolk (10%), 15 g standard diet (75%), and 2 ml fructose (1%). Thirty rats were randomized into five groups: C1 (normal control group), C2 (metabolic syndrome control group without treatment), P1 (striped catfish oil at 0.08 ml/200 g BW/day), P2 (turmeric extract at 5.04 mg/kg BW/day), P3 (combination of striped catfish oil at 0.08 ml/200 gBW/day and turmeric extract at 5.04 mg/kg BW/day). There was a significant decrease (p<0.05) in TNF-α levels and HOMA-IR in treatment groups (P1, P2, P3) compared to C2. The P3 group had the lowest TNF-α levels. Treatment groups had the same potential effect in reducing HOMA-IR. Striped catfish oil, turmeric extract, and their combination reduce inflammation and insulin resistance in metabolic syndrome rats.